Birth Defect Co-Occurrence Patterns Among Infants With Cleft Lip and/or Palate. (April 2022) - Sanchez, Maria Luisa Navarro; Benjamin, Renata H.; Mitchell, Laura E.; Langlois, Peter H.; Canfield, Mark A.; Swartz, Michael D.; Scheuerle, Angela E.; Scott, Daryl A.; Northrup, Hope; Schaaf, Christian P.; Ray, Joseph W.; McLean, Scott D.; et al.
Objective: To investigate 2- to 5-way patterns of defects co-occurring with orofacial clefts using data from a population-based registry. Design: We used data from the Texas Birth Defects Registry for deliveries between 1999 and 2014 to Texas residents, including 1884 cases with cleft palate (CP) and 5289 cases with cleft lip with or without cleft palate (CL±P) without a known syndrome. We identified patterns of defects co-occurring with CP and with CL±P observed more frequently than would be expected if these defects occurred independently. We calculated adjusted observed-to-expected ( O / E ) ratios to account for the known tendency of birth defects to cluster nonspecifically. Results: Among infants without a syndrome, 23% with CP and 21% with CL±P had at least 1 additional congenital anomaly. Several combinations of defects were observed much more often than expected. For example, the combination of CL±P, congenital hydrocephaly, anophthalmia, and other nose anomalies had an O / E ratio of 605. For both CP and CL±P, co-occurrence patterns with the highest O / E ratios involved craniofacial and brain abnormalities, and many included the skeletal, cardiovascular, and renal systems. Conclusions: The patterns of defects we observed co-occurring with clefts more often than expected may help improve our understanding of the relationships between multiple defects. Further work to better understand some of the top defect combinations could reveal new phenotypic subgroups and increase our knowledge of the developmental mechanisms that underlie the respective defects.